Arthroscopic Debridement For Degenerative Knee Joint Disease - Karn, Navin; Gupta, Ranjib Kumar; Gupta, Yogendra; Mishra, Bibhuti Nath (Nepal Orthopaedic Association Journal, 2016)
INTRODUCTION: Osteoarthritis of the knee is a common problem. Arthroscopic debridement of the knee can be a useful procedure when NSAIDs, physiotherapy and life style alterations arenot helpful in relieving the patient’s pain in mild to moderate osteoarthritis. This study was conducted to assess the result of arthroscopic debridement in OA knee. MATERIAL AND METHODS: 30 patients with mild to moderate osteoarthritis of the knee were treated by arthroscopic debridement. All the patients were followed at 2, 6, 12 and 24 weeks postoperatively. Functional outcome of knee was assessed by using modified WOMAC index and pain by visual analogue scale. RESULTS: 4% had had a previous meniscectomy and 61 % had a tear of at least one meniscus. Additional pathologic problems included loose bodies in 21 %, intra-articular adhesions in 10% and chondrocalcinosis in 6%. Post operatively, two patients had knee swelling lasted for three days and one had incision site erythema that subsided after a week. Subjectively, 83 percent of the patients were found to have good or fair results. CONCLUSION: Arthroscopic debridement of the knee joint is a useful short term therapeutic treatment modality in patients with mild to moderate degenerative arthritis of the knee.